Prognostic indicators for in-hospital mortality in COPD with acute exacerbation in Thailand: a retrospective cohort study - Thotsaporn Morasert (2020)
© Author(s) (or their employer(s)) 2020. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ. Background Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is a common and deteriorating event leading to in-hospital morbidity and mortality. Identification of predictors for in-hospital mortality of AECOPD patients could aid clinicians in identifying patients with a higher risk of death during their hospitalisation. Objective To explore potential prognostic indicators associated with in-hospital mortality of AECOPD patients. Setting General medical ward and medical intensive care unit of a university-affiliated tertiary care centre. Methods A prognostic factor research was conducted with a retrospective cohort design. All admission records of AECOPD patients between October 2015 and September 2016 were retrieved. Stratified Cox's regression was used for the primary analysis. Results A total of 516 admission records of 358 AECOPD patients were included in this study. The in-hospital mortality rate of the cohort was 1.9 per 100 person-day. From stratified Cox's proportional hazard regression, the predictors of in-hospital mortality were aged 80 years or more (HR=2.16, 95% CI: 1.26 to 3.72, p=0.005), respiratory failure on admission (HR=2.50, 95% CI: 1.12 to 5.57, p=0.025), body temperature more than 38°C (HR=2.97, 95% CI: 1.61 to 5.51, p=0.001), mean arterial pressure lower than 65 mm Hg (HR=4.01, 95% CI: 1.88 to 8.60, p<0.001), white blood cell count more than 15 x 10 9 /L (HR=3.51, 95% CI: 1.90 to 6.48, p<0.001) and serum creatinine more than 1.5 mg/dL (HR=2.08, 95% CI: 1.17 to 3.70, p=0.013). Conclusion Six independent prognostic indicators for in-hospital mortality of AECOPD patients were identified. All of the parameters were readily available in routine practice and can be used as an aid for risk stratification of AECOPD patients.